Transform Coefficient Coding for Screen Content in Versatile Video Coding (VVC) - Abdoli, Mohsen; Henry, Felix; Brault, Patrice; Dufaux, Frederic; Duhamel, Pierre (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2019)
A transform coefficient coding scheme is proposed for 4 × 4 blocks in Versatile Video Coding (VVC), targeting screen content applications. The proposed algorithm, called Unary Bitplane Coding (UBC), uses unary codes of the coefficient amplitudes and represents each block by their bitplanes. This representation allows exploiting further contextual information for source separation during the entropy coding. Experiments in the Joint Exploration test Model (JEM) show that replacing the existing transform coding with UBC only for 4 × 4 blocks brings on average 2.8% and 3.4% BD-R gain in the random access and all intra modes, respectively.